DUKUNGAN SOSIAL DAN KUALITAS HIDUP FISIK PEREMPUAN KORBAN KEKERASAN DALAM RUMAH TANGGA - Christy N M Hitijahubessy; Yati Affiyanti; Tri Budiati (Poltekkes Kemenkes Maluku, 2018)
Violence against women is generally a social phenomenon that is very worrying throughout the world,so WHO has established it as a global epidemic. Violence against women in the household, both inurban and rural areas, always places women in a vulnerable position which results in a lack ofconfidence and inhibits women from empowering themselves. The importance of social support greatlyhelps women victims of domestic violence to improve their quality of life. This study aims to identifysocial support to improve the physical quality of life of women victims of domestic violence. Thedesign of this study is cross-sectional. The study sample consisted of 243 women victims of domesticviolence, aged 19-49 years. Assessment of social support using the Multidimensional Scale ofPerseived Social (MSPSS) questionnaire, while an assessment of physical quality of life usingquestionnaire The World Health Organization Quality of Life (WHOQOL) Bref the Indonesianversion. The results of the analysis show that there is a very strong relationship, the direction of thepositive relationship between social support with the quality of physical life is affected (R = 0.994, p =0.000). Social support can be used as an intervention to improve the physical quality of life of womenvictims of domestic violence through mentoring and counseling programs. Keywords: Social support, quality of physical life, women victims of domestic